Association between gastroesophageal reflux disease and DMFT index in the PERSIAN Guilan Cohort Study - Mohammad Samami; Elham Jafari; Soheil Hassanipour; Mohammadreza Naghipour; Farahnaz Joukar; Fariborz Mansour-Ghanaei (Scientific Reports)
Abstract Studies investigating the association between gastroesophageal reflux disease (GERD) and the decayed, missing, and filled teeth (DMFT) index have yielded contradictory results. Therefore, this study aimed to determine this relationship in the PERSIAN Guilan Cohort Study (PGCS) population. This analytical cross-sectional study was part of the PGCS. Demographic, clinical, and oral hygiene information were collected. DMFT scores were specified by clinical examination, and GERD status was determined based on self-reported symptoms and confirmation by a medical specialist. Among 10,520 individuals in the PGCS, 13.2% (95% CI 12.5–13.8%) were diagnosed with GERD. The mean DMFT for the GERD group was 14.41 ± 8.47 and 14.59 ± 8.82 for the non-GERD group, and the difference was not statistically significant (P = 0.49). Linear regression analysis showed that older age, lower education and body mass index (BMI), smoking, alcohol consumption, higher wealth score index (WSI), and not tooth brushing were associated with an increased DMFT in the GERD group (P < 0.05). Findings indicate no association between GERD and an increased risk of dental caries in PGCS. These results should be interpreted cautiously, and longitudinal studies are needed to understand this relationship. The results demonstrated that tooth brushing exerts a substantial influence on both groups.